Tendons Trauma, Inflammation, Degeneration, and Treatment - Rosenberg, Nahum (IntechOpen, 2023)
The biological and mechanical connection between muscles and bones is made by tendon tissue. The physiological function of tendons is to enable joint movements by transmitting the force of muscle contraction. Due to their connective tissue content, tendons have semi-elastic properties and are thus vulnerable to structural failure and inflammatory degeneration, both of which have extremely disabling effects, particularly pain and hampered joint function. This book examines the causes of mechanical and inflammatory structural pathologies of the tendons and related therapeutic approaches for managing these injuries and conditions.